The Unmarked and the Marked: Qualifying Existence with Impredicative Hierarchies - Monga, Anubhav (Cosmos and History: The Journal of Natural and Social Philosophy, 2025)
This paper is about models (scientific, psychoanalytic, linguistic, theological or yet otherwise) and about how by ignoring the epistemological and metaphysical implications of the modelling process so ubiquitous in the scientific paradigm of today, we have not only hindered our understanding of phenomena from growing but completely misunderstood the nature of the most fundamental phenomena of being. Notably, the distinction between model and the modelled, or self and the Other is a primordial distinction any model-making edifice has to consider, lest the blowback of negative feedback disentangles the integrity of the model.